Non-physiological antioxidants: How safe? - Islam, Muhammad (International Journal of Medicine, 2017)
Antioxidants of various origins, by these days are one of the known health promotion tools in the world. These are also vastly used as over-the-counter medications. Having a protective capacity, antioxidants have been procured much attention in various fields; these include- dietary consumption, medicinal and cosmetic preparations, food and drinks preparation and preservation, and so on. Antioxidants are more concerned with the medical and pharmaceutical fields, where therapeutic applications are the prime apprehension. Our body has a number of antioxidants called physiological antioxidant systems. Generally, antioxidants are the reducing agents. A failure of balance between the production of oxidative substances and internal or physiological antioxidant molecules asks us to intake external or non-physiological antioxidants. How safe the non-physiological antioxidants? This text sketches theoretically a short scenario on safety and precautions of biologically installation of non-physiological antioxidants. This article is an update of previously published article by EC Orthopaedics 5.2 (2017): 29-31, where the author reserves all rights.